Investments and costs of oral health care for Family Health Care - Márcia Stefânia Ribeiro Macêdo; Sônia Cristina Lima Chaves; Antônio Luis de Carvalho Fernandes (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To estimate the investments to implement and operational costs of a type I Oral Health Care Team in the Family Health Care Strategy. METHODS This is an economic assessment study, for analyzing the investments and operational costs of an oral health care team in the city of Salvador, BA, Northeastern Brazil. The amount worth of investments for its implementation was obtained by summing up the investments in civil projects and shared facilities, in equipments, furniture, and instruments. Regarding the operational costs, the 2009-2012 time series was analyzed and the month of December 2012 was adopted for assessing the monetary values in effect. The costs were classified as direct variable costs (consumables) and direct fixed costs (salaries, maintenance, equipment depreciation, instruments, furniture, and facilities), besides the indirect fixed costs (cleaning, security, energy, and water). The Ministry of Health's share in funding was also calculated, and the factors that influence cost behavior were described. RESULTS The investment to implement a type I Oral Health Care Team was R$29,864.00 (US$15,236.76). The operational costs of a type I Oral Health Care Team were around R$95,434.00 (US$48,690.82) a year. The Ministry of Health's financial incentives for investments accounted for 41.8% of the implementation investments, whereas the municipality contributed with a 59.2% share of the total. Regarding operational costs, the Ministry of Health contributed with 33.1% of the total, whereas the municipality, with 66.9%. Concerning the operational costs, the element of heaviest weight was salaries, which accounted for 84.7%. CONCLUSIONS Problems with the regularity in the supply of inputs and maintenance of equipment greatly influence the composition of costs, besides reducing the supply of services to the target population, which results in the service probably being inefficient. States are suggested to partake in funding, especially to cover the team's operational cost.